2022
DOI: 10.1186/s12859-022-04842-4
|View full text |Cite
|
Sign up to set email alerts
|

A binary biclustering algorithm based on the adjacency difference matrix for gene expression data analysis

Abstract: Biclustering algorithm is an effective tool for processing gene expression datasets. There are two kinds of data matrices, binary data and non-binary data, which are processed by biclustering method. A binary matrix is usually converted from pre-processed gene expression data, which can effectively reduce the interference from noise and abnormal data, and is then processed using a biclustering algorithm. However, biclustering algorithms of dealing with binary data have a poor balance between running time and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The SDI evolutionary tree highlighted the internal distinctions of SARS-CoV-2, whereas the SDII evolutionary tree compared SARS-CoV-2 to other HCoVs and SARSr-CoV-2 lineages to explore their genetic evolution rules. The phylogenetic results of SDs demonstrated that the internal nodes in trees and the clustering algorithm for adjacency matrix ( Chu et al., 2022 ) had little effect on the classification of certain species, which intuitively displayed excessively long branches in the tree due to poor sequencing quality of a few sequences. Internal nodes of the tree ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SDI evolutionary tree highlighted the internal distinctions of SARS-CoV-2, whereas the SDII evolutionary tree compared SARS-CoV-2 to other HCoVs and SARSr-CoV-2 lineages to explore their genetic evolution rules. The phylogenetic results of SDs demonstrated that the internal nodes in trees and the clustering algorithm for adjacency matrix ( Chu et al., 2022 ) had little effect on the classification of certain species, which intuitively displayed excessively long branches in the tree due to poor sequencing quality of a few sequences. Internal nodes of the tree ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Certain overlapping biclustering models are able to capture member clusters contained in two or more biclusters in the data matrix. Such methods have been applied to many biological data for the classification and identification of biological entities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, Wang et al (2016) argue that biclustering algorithms are non-specific so there is no rule how to choose the right one for certain criteria or datasets. The selection of a biclustering algorithm should be based on several considerations, namely ease of implementation, absence of disturbance by noisy datasets and speed in finding the most suitable structure in the data matrix (Castanho et al, 2022;Chu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%